2004
DOI: 10.4321/s1699-65852004000100005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación clínica, microbio lógica e inmuológica de la ozonoterapia en pacientes con bolsas periodontales moderadas-severas

Abstract: INTRODUCCIÓN.En los últimos años se ha producido un progreso importante en el conocimiento de la enfermedad periodontal, desde su etiología multifactorial, la microbiología responsable, la respuesta inmunológica local, así como múltiples aspectos en relación con su epidemiología, etiopatogenia y su proceso evolutivo. Dado el mayor conocimiento en estos campos, se desarrollan nuevas técnicas, productos farmacológicos y técnicas que tratan de detener la enfermedad periodontal y preservar la salud bucal.OBJETIVOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Treatment studied showed a good efficacy by 85, 4% in the total sample, predominating in the experimental group D (combined ozone therapy treatment) and being less in control group with significant statistical differences between the control group and the experimental ones. The same results were obtained by Ripollés de Ramón J y col. 44 at analyzing the periodontal responses from a clinical, microbiologic and immunologic point of view of a population with severe moderate periodontal pockets and their comparison, after ozone therapy with the technique of radicular scraping and smoothing. They found that periodontal treatment with ozone produces a significant statistical reduction of Lindhe Index for gingival bleeding, in the periodontal pathogenic microbiology, as well as in the immunologic patterns of IL1-b y el TNF-alfa.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment studied showed a good efficacy by 85, 4% in the total sample, predominating in the experimental group D (combined ozone therapy treatment) and being less in control group with significant statistical differences between the control group and the experimental ones. The same results were obtained by Ripollés de Ramón J y col. 44 at analyzing the periodontal responses from a clinical, microbiologic and immunologic point of view of a population with severe moderate periodontal pockets and their comparison, after ozone therapy with the technique of radicular scraping and smoothing. They found that periodontal treatment with ozone produces a significant statistical reduction of Lindhe Index for gingival bleeding, in the periodontal pathogenic microbiology, as well as in the immunologic patterns of IL1-b y el TNF-alfa.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…However, they do not coincide with our study regarding the level of periodontal insertion and depth of the periodontal pocket. There are experimental works 45,46 in models of endotoxic clash and lethal peritonitis where it is achieved, by means of application through rectal way, a reduction of specific pro inflammatory cytokines(IL-1, TNF-alfa), coinciding with what has been reported by Ripollés de Ramón J y col. 44 In the studies reported by the reviewed literature [35][36][37][38][39][40][41][42]44 there are not adverse events detected in the clinical trials, it is only commented on the possibility of a slight cough when ozone gas is employed, mainly when not all the necessary measures are taken during handling or if the patient is asthmatic or suffers from respiratory problems which constitutes one of the precautions of this modality. It has also been spoken of dryness of the laryng and in isolated cases of burning sensation, pruritus; coinciding with the study carried out where the percentage of adverse effects was very low.…”
Section: Discussion Of Resultsmentioning
confidence: 99%